2015
DOI: 10.1002/eji.201545784
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia‐inducible factor‐1α perpetuates synovial fibroblast interactions with T cells and B cells in rheumatoid arthritis

Abstract: Keywords: B cell r Hypoxia-inducible factor-1α r Rheumatoid arthritis r Synovial fibroblast r T cell Additional supporting information may be found in the online version of this article at the publisher's web-site

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(55 citation statements)
references
References 22 publications
0
55
0
Order By: Relevance
“…For example, the hypoxic conditions in RA synovium lead to the local production by FLS of hypoxia-inducible factor-1alpha, which alters FLS gene expression in multiple ways relevant to the pathogenesis of RA[104], including augmentation of production of pro-inflammatory cytokines and of interactions of FLS with both T and B cells. The pathogenesis of RA does not reflect the actions of any one cell lineage, but rather the complex interactions between all cell populations in RA synovium, mediated by both direct cell-cell contact and by molecules that are secreted or shed by the various types of synovial cells.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the hypoxic conditions in RA synovium lead to the local production by FLS of hypoxia-inducible factor-1alpha, which alters FLS gene expression in multiple ways relevant to the pathogenesis of RA[104], including augmentation of production of pro-inflammatory cytokines and of interactions of FLS with both T and B cells. The pathogenesis of RA does not reflect the actions of any one cell lineage, but rather the complex interactions between all cell populations in RA synovium, mediated by both direct cell-cell contact and by molecules that are secreted or shed by the various types of synovial cells.…”
Section: Resultsmentioning
confidence: 99%
“…HIF1α, a transcription factor that responds to reduced oxygen tension, is believed to have a central role in adaption to the hypoxic environment. Accumulating evidence proved that hypoxia and HIF1α regulate a number of pathophysiological characteristics of RA, including synovitis, angiogenesis, cartilage degradation and bone erosion . HIF1α has also been supposed to be a potential therapeutic target for RA .…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence proved that hypoxia and HIF1a regulate a number of pathophysiological characteristics of RA, including synovitis, angiogenesis, cartilage degradation and bone erosion. 30,32,39,40 HIF1a has also been supposed to be a potential therapeutic target for RA. 41 In the present study, we found inhibiting HIF1a significantly decreased the production of citrullinated F I G U R E 2 Hypoxia increases the production of PAD2 and citrullinated proteins in HFLS.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, there is evidence showing that HIF-1 α upregulates the expression of inflammatory cytokines including IFN- γ in synovial fibroblast of RA patients [23]. In this sense, IFN γ has been associated with more severe forms of SS, characterized by high grade infiltration of lymphocytes, macrophages, and dendritic cells as well as with gastric NHL lymphomas [24].…”
Section: Discussionmentioning
confidence: 99%